EXTRACELLULAR GLYCOLIPIDS FROM SACCHAROMYCES CEREVISIAE AS BIOEMULSIFYING AGENTS IN FOOD PROCESSING - SELVAKUMAR K; ANIBABIYANS ROYP; MADHAN R (Innovare Journal of Food Sciences, 2016)
The development of food processing sector and increasing diversity in consumers' taste has continuously put forth different demands in the interdisciplinary research. In this research study, a demand for bio-based emulsifying agent to improve the oil-aqueous based food has been taken as a predominant destination. Extracellular glycolipids were produced using Saccharomyces cerevisiae MTCC 181 strain and basic characterization studies were performed.Further, the scope of the partially purified bioemulsifier in food processing was examined using different experiments and found to be more promising.